The Role of Village-owned Enterprises (BUMDes) in Optimizing Village Funds in South Lampung District - Alhamidi; Varida Henemia Pakpahan; Hendro Muliarto (Bappenas Working Papers, 2018)
The purpose of this study is to see how to determine the BUMDes (Village-owned Enterprises) development strategy through optimizing the use of village funds in South Lampung District, Lampung Province. The study is conducted with interviews and questionnaires to the community in the village who would develop BUMDes. The methods used are descriptive analysis and SWOT. Some findings indicate that village-owned companies are needed to control the economy in the village.